Factors Associated with Premarital Sexual Practice among Adolescents in Kupang - Nomleni, Weli Maryati; Talahatu, Anna Henny; Limbu, Ribka (Media Kesehatan Masyarakat, 2023)
Premarital sexual behavior practice is deviant behavior that negatively affects the lives of teenagers; however, many teenagers are engaged in this behavior due to a lack of knowledge related to its causes and effects. This study aims to analyze the factors associated with premarital sexual behavior in adolescents. This research was an analytic survey with a cross-sectional design and was conducted at SMK Negeri Z Kupang with a sample of 322 students. The data were analyzed using the chi-square test. The result showed that knowledge of reproductive health (p-value= 0.006), attitude (p-value= 0.000), parenting style (p-value= 0.0060, peers (p-value= 0.001), and social media (p-value= 0.000) were associated with premarital sexual behavior while no relationship was identified between religiosity (p-value= 0.123) and the behavior. Schools need to reactivate the Youth Information and Counseling Center (PIK-R) so that teenagers can access information about reproductive health to prevent them from having sex before marriage.